Morphology of Ceriodaphnia rotunda (Straus, 1820) and C. laticaudata P.E. Müller, 1867 (Cladocera: Daphniidae) with comments on the importance of limb II characters for the genus taxonomy - Garibian, Petr G.; Varakina, Elizaveta D.; Neretina, Anna N.; Degtyareva, Elena K.; Kotov, Alexey A. (Zootaxa, 2026)
Representatives of the genus Ceriodaphnia Dana, 1853 (Cladocera: Daphniidae) are widely distributed worldwide, they are very common in the plankton of many freshwater bodies of different types in temperate and tropical latitudes. However, their taxonomy remains intricate, especially as compared to the genus Daphnia O.F. Müller, 1785. The aim of this study is to redescribe the morphology of Eurasian taxa having a specific (high and triangular) postabdomen, namely C. rotunda (Straus, 1820) and C. laticaudata P.E. Müller, 1867 and list the differences between these two taxa. A population from Republic of Sakha (Yakutia, Asian Russia) is identified as C. cf. laticaudata, and its exact taxonomic status could not be resolved to date due to a limited material and absence of gamogenetic specimens in our collection. Also, we analyse the morphological characters used for identification of common Eurasian taxa with special attention to limb II. All Ceriodaphnia species could be subdivided into four groups according to the size of anterior setae on the inner-distal portion of limb II: the pulchella-group with a single rudimentary seta on endite 4 and no seta on endite 3, the quadrangula group with short setae on endites 3 and 4, the dubia-turkestanica-reticulata-nikolaii group with a single very large seta on endite 4 and a shorter seta on endite 3, and the rotunda-laticaudata group with large setae on endites 4 and 3. Four aforementioned groups could be formed according to ecological preferences rather than their phylogenetic position. A further step-by-step revision of Ceriodaphnia is needed based on morphological and full-genome data for adequate understanding of the genus diversity.